NFT Marketplaces : User Experience and Usability Challenges - Tkačik, Vladislav; Kania, Karolina Anna; Balata, Jan; Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky (2025)
Through the use of the Design Thinking process, this thesis explores the experiences of NFT artists within the NFT space, focusing on the challenges and opportunities they face while creating and selling artworks through NFT marketplace platforms. The study aims to uncover artists’ perspectives that can inform new opportunities for creating better NFT marketplace experiences. Through a series of seven semi-structured interviews with artists active in the NFT space, insights were gathered about their motivations, needs and goals, along with challenges and usability problems they face when creating and selling NFTs on these platforms. One of the key findings was that NFT artists struggle with community building, which they perceive as crucial for their success. Another finding revealed that they see NFT marketplaces primarily as sales intermediaries where the final step of the sale transaction happens, and they offer limited community engagement tools. Based on these findings, a key problem was identified regarding the lack of community- building tools. Various ideas to address this issue were explored, resulting in the development of an auction page prototype for the NFT marketplace KodaDot, which is a community-driven project operating in the Polkadot ecosystem. The design included features like emoji reactions, live chat with the artist, and a behind-the-scenes section to share the story behind the art. These ideas were tested with artists and collectors to see their usefulness and engagement. The feedback showed that simple interactions and direct artist connection can improve the overall user experience.
Vedoucí práce: Karolina Anna Kania
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: vývoj informačních systémů [obor dipl. práce]; diplomové práce; master's theses